Uncover the meaning of figurative language in the selected songs - Teja, Nova Surya; Utami, Ni Made Verayanti; Juniartha, I Wayan (Yayasan Mitra Persada Nusantara, 2022)
Language is the main medium for communication, and can build relationships with each other that serve to carry meaning. This study concerns to analyze figurative languages found in selected Alec Benjamin song lyrics. There are two problems that are formulated in this study, they are: (1) what are the types of figurative language found in Alec Benjamin song lyrics; (2) what are the meaning of the Figurative language found in Alec Benjamin song lyrics. In this research used two theories. The first theory proposed by Knickerbocker and Reninger (1963) which is used to identify figurative language types and the second theory of meaning is supported by Leech (1981) to analyze the meaning. The method used in gathering the data was done by the method of formal and informal. The researcher obtained the data by listening the songs, reading the scripts of lyrics, underlining, and classifying the lyrics which contains types of figurative languages. The data was analyzed descriptively using qualitative method. It was found four types of figurative language: hyperbole, personification, synecdoche, and paradox. The most widely used is hyperbole and simile, with the rest has equal numbers or rank. There is one type of meaning found in the lyrics in a connotative meaning.